New Perspective: Measuring Auditor Professionalism in Fraud Detection - Heni, Heni; Sayekti, Yosefa; Maria Wardayati, Siti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This research provides a new point of view to measure the professionalism of BPKP auditors in the field of investigation by utilizing the professionalism stated in the Regulation of the Head of BPKP 2010. The research was conducted on BPKP auditors in Java and Bali by filling out a questionnaire distributed via google form. From the distributed questionnaire obtained 51 respondents who participated in this study. Based on the data obtained, hypothesis testing was carried out using the Structural Equation Model (SEM) with the SmartPLS version 3.2.6 software. The results prove that auditor professionalism has a positive and significant effect on fraud detection as evidenced by the t-statistic of 7.526. In other words, the higher the professionalism of the investigative BPKP auditors, the higher their ability to detect fraud. The results also prove that professionalism according to the Regulation of the Head of the BPKP Year 2010 has been carried out properly by the BPKP auditors in the field of investigation and has truly become a work culture that must be carried out.